Confirmation of the presence of Epidendrum purpureocaulis (Orchidaceae) in Brazil and expansion of its geographic distribution to the State of Pará - David Ferreira da Silva; Erlediel Gusmão do Nascimento; Daniela Cristina Zappi; Felipe Fajardo Villela Antolin Barberena (Hoehnea)
ABSTRACT Epidendrum purpureocaulis is a recently described species, belonging to the group Epidendrum nocturnum, and was previously known only from French Guiana. Epidendrum ancipitinocturnum was described from the Brazilian State of Amazonas, and was later recognized as conspecific with E. purpureocaulis by several orchidologists, a position with which we agree. However, the occurence of E. purpureocaulis in Brazil is not included in the main global botanical databases since E. ancipitinocturnum has been treated as an autonomous species or even as a synonym of Epidendrum carpophorum in these databases. Our objective is to confirmate the occurrence of E. purpureocaulis in Brazil and report the expansion of its geographic distribution to the State of Pará. We found a small population of E. purpureocaulis in a transition area between campinarana and terra firma forest vegetacional types in the municipality of Cachoeira do Arari, Marajó Island, in the Brazilian Amazon. The collected specimen represents the easternmost distribution record of E. pupureocaulis, being approximately 650 kilometers away from its nearest location. Field efforts have been intensified in Cachoeira do Arari in order to identify new populations and better understand the ecological requirements of E. purpureocaulis.